Bioplastics: known effects and potential consequences to marine and estuarine ecosystem services. (December 2022) - Venâncio, Cátia; Lopes, Isabel; Oliveira, Miguel
Abstract: Bioplastics have been suggested as more sustainable alternatives to conventional, petroleum-based plastics. In this work, the available studies comparing effects of biopolymers and petroleum-based plastics were reviewed to improve the knowledge on the sustainability of biobased polymers, providing a benchmark regarding their ecotoxicological effects, as well as to highlight research priorities in this field. The literature review shows that, only a small number of the available biopolymers have been tested highlighting the need for more research diversifying the tested polymers. Overall, the available studies support the idea that bioplastics are likely to cause physiological impairments (feeding, reproduction, or locomotion) as well as cellular (proteome and enzyme activity) effects on biota. Furthermore, the studies on bioplastic degradation under realistic conditions report changes in water and sediment quality, which may also have consequences to biota. It is evident that some reservations must be kept regarding conventional plastics substitutions by bioplastics. Graphical abstract: Image 1 Highlights: Reported effects of bioplastics on coastal ecosystems were reviewed. PLA and Mater-bi® bags are the most studied bioplastics. Overall, effects induced by bioplastics are similar to those of conventional plastics. Balance between bioplastic production and sustainability is a major problem. Precautionary measures must be taken in relation to commercialization of bioplastics.